2단계 촉매 분해공정을 이용한 리그닌 유래 선택적 페놀화합물 생산 - 김재영; Jae-young Kim; 허수정; Sujung Heo; 박신영; Shin Young Park; 최인규; In-gyu Choi; 최준원; Joon Weon Choi (목재공학, 2017)
본 연구에서는 2단계 촉매 분해공정 시스템을 이용하여 효과적으로 리그닌을 분해하였으며 리그닌 분해산물로 액상의 리그닌 오일, 촤, 가스가 생성되었다. 1차 촉매 분해공정에서는 MgO, CaO, Pt/C 촉매를 사용하였으며 Pt/C 촉매를 사용했을 때 가장 높은 리그닌 오일 수율(76.2 wt%) 및 가장 낮은 촤 수율(4.1 wt%)을 얻을 수 있었다. 리그닌 오일의 GC-MS/FID 분석을 통해 guaiacol, 4-ethylphenol, 4-methylguaiacol, 4-ethylguaiacol, syringol 등 18종류의 페놀화합물을 검출하였으며 Pt/C 조건에서 생산된 페놀화합물 수율이 97.8 mg/g lignin로 가장 높았다. 한편 MgO와 CaO에서 생산된 페놀화합물은 촉매에 흡착되어 상대적으로 낮은 수율을 보였다. Pt/C 조건에서 생산된 리그닌 오일을 다공성 구조를 가지는 Pd/activated carbon aerogel 촉매 하에서 추가 분해하였다. 2차 촉매 분해공정을 통해 상대적으로 선택성이 높은 4가지 페놀화합물(4-ethylguaiacol, 4-propylguaiacol, 4-ethylsyringol, 4-propylsyringol)을 0.89 - 1.82 wt% 수준으로 생산하였다. In this study, lignin was efficiently degraded via two-step catalytic cracking process and lignin-oil, char, and gas was produced as lignin degraded products. Three kinds of catalysts (MgO, CaO, and Pt/C) were used in first catalytic cracking step and the highest lignin-oil yield (76.2 wt%) was obtained in Pt/C catalyst with the smallest char formation (4.1 wt%). GC-MS/FID analysis revealed that 18 kinds of monomeric phenols existed in lignin-oil and sum of them was the highest in Pt/C condition (97.8 mg/g lignin). Meanwhile, relatively lower yield of monomeric phenols was produced in MgO and CaO condition because of their absorption on catalysts. Lignin-oil produced over Pt/C was introduced to second catalytic cracking process with porous Pd/activated carbon aerogel catalyst. From this process, four kinds of monomeric phenols such as 4-ethylguaiacol, 4-propylguaiacol, 4-ethylsyringol, 4-propylsyringol were selectively produced at 0.89 - 1.82 wt% level.